Centennial-Scale SE Pacific Sea Surface Temperature Variability Over the 2,300 Years - Collins, James A.; Lamy, Frank; Kaiser, Jerome; Ruggieri, Nicoletta; Henkel, Susann; De Pol Holz, Ricardo Hernán; Garreaud, Rene; Arz, Helge W. (My University, 2019)
Detailed temperature reconstructions over the past 2,000 years are important for contextualizing modern climate change. The midlatitude SE Pacific is a key region in this regard in terms of understanding the climatic linkages between the tropics and southern high latitudes. Multicentennial timescale temperature variability remains, however, poorly understood, due to a lack of long, high-temporal-resolution temperature records from this region and from the southern high latitudes in general. We present a unique alkenone sea surface temperature (SST) record from 44 degrees S on the southern Chilean margin in the SE Pacific spanning the last 2,300 years at decadal resolution. The record displays relatively large changes including a cooling transition from 14 to 12.5 degrees C between 1,100 and 600 cal yr BP, in line with other Chile margin SST records and coeval with Antarctic cooling. This cooling is attributable to reduced Southern Ocean deep convection, driven by a late Holocene sea-ice increase in the Weddell Sea associated with increased El-Nino Southern Oscillation variability. Superimposed on the late Holocene cooling, we observe multicentennial timescale SST variability, including relatively cool SSTs (12.5 degrees C) from 950 to 500 cal yr BP, corresponding to the Medieval Climate Anomaly, and warmer SSTs (13 degrees C) from 500 to 200 cal yr BP, corresponding to the Little Ice Age. These oscillations may reflect either multicentennial internal variability of the Southern Ocean deep convection and/or multicentennial variability in the phasing of El-Nino Southern Oscillation and Southern Annular Mode events.
Keywords: Middle latitudes; Anomaly (physics)